METODE PEMBELAJARAN GURU PAK DALAM UPAYA MENINGKATKAN KEAKTIFAN SISWA PADA KEGIATAN BELAJAR DI SMA NEGERI 3 SURAKARTA - Yoarita Pambudiyana; Justin Niaga Siman Juntak (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Student activeness is one of the important indicators in determining the success of the learning process. However, student participation in Christian Religious Education (CRE) learning is still varied, with some students tending to be passive during classroom activities. This study aimed to describe the learning methods used by Christian Religious Education teachers to improve student activeness at SMA Negeri 3 Surakarta. The research employed a descriptive qualitative approach with a field research design. Data were collected through observations, interviews, and documentation involving one Christian Religious Education teacher and ten Christian students from grades X and XI. Data were analyzed using the Miles and Huberman model through data collection, reduction, display, and conclusion drawing. The results showed that CRE learning has moved toward communicative and active learning through the implementation of sharing, question-and-answer, and group discussion methods. Teachers also attempted to increase student participation through ice-breaking activities and individual as well as group assignments. Supporting factors included the use of PowerPoint presentations, group collaboration, and opportunities for students to express their opinions. Meanwhile, inhibiting factors consisted of boredom, lack of self-confidence, difficulties in understanding learning materials, and limited variation in learning media.